Analyzing the Effects of Intrauterine Hypoxia on Gene Expression in Oocytes of Rat Offspring by Single Cell Transcriptome Sequencing - Li, Ting; Liu, Yang; Yue, Shaojie; Liao, Zhengchang; Luo, Ziqiang; Wang, Mingjie; Cao, Chuanding; Ding, Ying; Lin, Ziling (Frontiers in Genetics, 2019)
Intrauterine hypoxia is one of the most frequently occurring complications during pregnancy, and the effects of antenatal hypoxia in offspring are not restricted to the perinatal period. Previous studies have reported on this phenomenon, which is usually described as multigenerational or transgenerational inheritance. However, the exact mechanism of this type of inheritance is still not clear. Therefore, in the present study, we investigated the alteration in the gene expression of oocytes, derived from intrauterine hypoxia rats and their offspring, by single cell transcriptome sequencing. Our results showed that 11 differentially expressed genes (DEGs) were inherited from the F1 to F2 generation. Interestingly, these DEGs were enriched in processes predominantly involved in lipid and insulin metabolism. Overall, our data indicated that alteration in the gene expression of oocytes may be associated with some metabolic diseases and could potentially be the basis of transgenerational or multigenerational inheritance, induced by an adverse perinatal environment.